Case Report: Deficiency of Adenosine Deaminase 2 Presenting With Overlapping Features of Autoimmune Lymphoproliferative Syndrome and Bone Marrow Failure - Dell’Orso, Gianluca; Grossi, Alice; Penco, Federica; Caorsi, Roberta; Palmisani, Elena; Terranova, Paola; Schena, Francesca; Lupia, Michela; Ricci, Erica; Montalto, Shana; Pierri, Filomena; Ceccherini, Isabella; et al. (Frontiers in Immunology, 2021)
Deficiency of Adenosine Deaminase 2 is an autosomal recessive disease associated with highly variable clinical presentation, such as vasculitis, inflammation, hematologic manifestations. Some associations of clinical features can mimic autoimmune lymphoproliferative syndrome (ALPS). We report a case of a female patient, who fulfilled the diagnosis of autoimmune lymphoproliferative disease (ALPS) according to 2009 National Institute of Health (NIH) revised criteria, lately diagnosed with DADA2 deficiency. During her childhood she suffered for autoimmune hemolytic anemia, immune thrombocytopenia and chronic lymphoproliferation, partially responding to multiple lines of treatments, followed, at 25 years of age, by pulmonary embolysm, septic shock and bone marrow failure with myelodisplastic evolution. The patient died due to progression of pulmonary disease and multiorgan failure. Two previously unreported variants on gene ADA2 were found through next-generation sequencing analysis and a pathogenic role was demonstrated through functional study. A single somatic STAT3 mutation was also found. Clinical phenotypes encompassing immune-dysregulation and marrow failure should be evaluated at the early stage of diagnostic work-up with an extended molecular evaluation. A correct genetic diagnosis may lead to a precision medicine approach consisting of the use of targeted treatments or pre-transplantation tailored conditioning regimen.